The Influence of Cultural Pride, Perceived Price, and Perceived Quality on Prestige and Brand Loyalty on Indonesia’s Batik - Widyarini, Lydia Ari; Heriman, Angelyna (Inovbiz: Jurnal Inovasi Bisnis, 2024)
Fashion is something that can’t be separated from human life. Batik can be categorized as a form of fashion that originated in Indonesia. Batik itself is a traditional Indonesian fabric that originated on the island of Java. Batik cloth has unique characteristics that other types of cloth do not have. Over time, batik has become increasingly in demand in the community because it can be used for formal and non-formal clothing. The aim of this study is to examine the impact of cultural pride, perceived price, and perceived quality on prestige, as well as the relationship between prestige and brand loyalty on Batik Keris. Batik Keris is known as one of the biggest batik companies in Indonesia. The data for this study was collected through a Google Form survey. The researcher gathered responses from 154 individuals residing in Surabaya, aged above 17 years old, who had purchased Batik Keris fashion products for at least the last year and had a monthly expenditure of ≥Rp. 1.200.000,00. The collected data was then processed using Smart PLS 3.0 and analyzed through the Structural Equation Model (SEM) method. The findings of the study indicate that cultural pride doesn’t have any influence on prestige, whereas perceived price and perceived quality have a significant influence on prestige. Additionally, prestige also exerts a significant influence on brand loyalty.